An algebra problem by Alex Harman

Algebra Level 3

x 2 18 x 18 9 = 144 14 x 2 x 2 \large \frac { { x }^{ 2 }-18x-18 }{ 9 } =\frac { 144-14x^2 }{ { x }^{ 2 } }
Solve for positive integer x x .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Jul 12, 2016

x 2 18 x 18 9 = 144 = 14 x 2 x 2 x 4 18 x 3 18 x 2 = 1296 126 x 2 x 4 18 x 3 + 108 x 2 = 1296 Divide both sides by x 2 . x 2 18 x + 108 = 1296 x 2 \begin{aligned} \frac {x^2-18x-18}9 & = \frac {144=14x^2}{x^2} \\ x^4-18x^3-18x^2 & = 1296 - 126x^2 \\ x^4 - 18x^3 + 108x^2 & = 1296 \quad \quad \small \color{#3D99F6}{\text{Divide both sides by }x^2.} \\ x^2 - 18x + 108 & = \frac {1296}{x^2} \end{aligned}

Since x x is an positive integer, the LHS is integral, therefore, the RHS must also be integral. This means that x 2 1296 = x 2 2 4 3 4 x^2|1296 = x^2|2^43^4 , implying that x x is a multiple of 2 and/or 3, since it is obvious that x 1 x \ne 1 . And when:

x = 2 : 2 2 18 ( 2 ) + 108 = 1296 2 2 76 324 \begin{aligned} x = 2: \quad 2^2 - 18(2) + 108 & = \frac {1296}{2^2} \\ 76 & \ne 324 \end{aligned}

x = 3 : 63 144 x = 6 : 36 = 36 \begin{aligned} x = 3: \quad 63 & \ne 144 \\ x = 6: \quad 36 & = 36 \end{aligned}

x = 6 \implies x = \boxed{6}

Alex Harman
Jul 9, 2016

I'm not going to lie, It took me awhile to figure out a way to prove this after making the problem. It's a tricky one.
x 2 18 x 18 9 = 144 14 x 2 x 2 x 2 9 2 x 2 = 144 x 2 14 x 2 9 144 x 2 ( 2 x 12 ) = 0 x 4 1296 9 x 2 ( 2 x 12 ) = 0 ( x 2 36 ) ( x 2 + 36 ) 9 x 2 2 ( x 6 ) = 0 ( x 6 ) ( x + 6 ) ( x 2 + 36 ) 9 x 2 2 ( x 6 ) = 0 ( 6 4 1296 ) 9 ( 6 2 ) 2 ( 6 6 ) = 0 \frac { { x }^{ 2 }-18x-18 }{ 9 } =\frac { 144-14x^{ 2 } }{ { x }^{ 2 } } \\ \frac { { x }^{ 2 } }{ 9 } -2x-2=\frac { 144 }{ { x }^{ 2 } } -14\\ \frac { { x }^{ 2 } }{ 9 } -\frac { 144 }{ { x }^{ 2 } } -(2x-12)=0\\ \frac { { x }^{ 4 }-1296 }{ 9{ x }^{ 2 } } -(2x-12)=0\\ \frac { \left( { x }^{ 2 }-36 \right) \left( { x }^{ 2 }+36 \right) }{ 9{ x }^{ 2 } } -2(x-6)=0\\ \frac { \left( x-6 \right) (x+6)\left( { x }^{ 2 }+36 \right) }{ 9{ x }^{ 2 } } -2\left( x-6 \right) =0\\ \frac { \left( { 6 }^{ 4 }-1296 \right) }{ 9\left( { 6 }^{ 2 } \right) } -2(6-6)=0

Edwin Gray
Jul 30, 2018

Cross multiplying, x^4 - 18x^3 + 108x^2 - 1296 =0. Let x + 6t, getting: 1296t^4 - 3888t^3 + 3888t^2 - 1296 = 0. Dividing by 1296, t^4 - 3t^3 + 3t^2 - 1 =0,which has the obvious root t =1, so x = 6. Further division reveals this is a multiple root. Ed Gray

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...